EP325 In case of an unusual cervical mass: think to lymphoma. (1st November 2019) - Kilzie, S; Pezzani, I; Sartori, F; Rossi, A; Busato, E
Abstract : Introduction/Background: We present the case of a 46 year-old woman with a rare gynecological presentation of an aggressive lymphoma. Methodology: Case report. Results: A 46 year-old woman is referred to the hospital for presenting leucorrea and irregular copious vaginal bleeding; she denies other symptoms. At the physical examination a solid and fixed mass deforming the cervix is observed and the posterior vaginal wall appears thickened. The transvaginal ultrasound shows a solid and vascularized (colour score 4) image of 94 × 6565 mm. The MRI confirms the presence of a pelvic mass at the cervix of 10 × 9 × 10 cm with necrotic areas. Other iliac, presacral and inguinal lymphadenopathies are identified by PET scan. Hysteroscopy identifies two typical endocervical polyps and a normal endometrium. Biopsies are realized directly at the surface of the visible lesion through speculum examination. The anatomopathological analysis reveals a diffuse Large B-cell lymphoma so the patient is remitted to the Haematologist to complete the staging and start the chemo-immunotherapy. Conclusion: Hematologic malignancies rarely present as a primary gynaecologic problem and primary gynaecologic Non-Hodgkin Lymphoma are sporadically reported in the literature. Primary NHL can mimic gynaecological malignancy such as endometrial cancer, cervical cancer, sarcoma or ovarian cancer presenting as a pelvic mass. The primary site of origin for lymphomas is the lymph nodes and other lymphoid tissue but approximately 10 to 35% of patients have a primary extranodal lymphoma at the time of diagnosis. Only less than 0.5% of all extranodal NHLs involve the female genital tract. Most patients lack the classical B symptoms associated with lymphoma: fatigue, fever, night sweats and weight loss. The primary pelvic lymphomas have a five-year survival rate of 80% to 90% if the diagnosis was made early and therapy was adequate so the diagnosis of primary pelvic lymphoma should be considered in the differential diagnosis of gynaecological malignancies. Disclosure: Nothing to disclose.